The OBJN upgrade: now it is the official journal of the Professional Master in Nursing Program at the Fluminense Federal University Nursing School! - Cruz, Isabel Cristina Fonseca da (Online Brazilian Journal of Nursing, 2004)
The OBJN complete three years communicating nursing research much more quickly, broadly, and openly than was possible through traditional print publications. With the OBJN, a scholarly publication, the Brazilian nursing articles may be easily found and freely shared. In its third volume, the OBJN is moving toward more comprehensive context. It is leaving the NAIG (NURSING ACTIVITIES INTEREST GROUP) to be administered by the Professional Master in Nursing Program at theFluminenseFederalUniversityNursingSchool.This upgrade will add value to the OBJN by enriching its editorial policy and linking the journal to a graduate program.Since 2001, the OBJN expanded its subscription to almost 2,000 subscribers. The OBJN have published authors fromBraziland abroad with the collaboration of a international Editorial Board. The OBNJ was included into important nursing and health references databases as LATINDEX, BIREME (LIS-Regional), CAPES (C-Nacional), CUIDEN, RealNurseNet, Nurselinx, UNIFESP, FreemedicalJournals, Nurses.info, DOAJ, Online Nurse Editors, and CINAHL.I am hopeful that the OBJN will be consolidate its trajectory under the coordination of the Professional Master in Nursing. To develop this task, we will have the professors and the graduate students collaboration.